2021
DOI: 10.1111/jfb.14846
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive biochemical characterization of settlement stage leptocephalus larvae of bonefish (Albula vulpes)

Abstract: Little is known about early development of the near-threatened bonefish (Albula vulpes), a member of superorder Elopomorpha. Members of Elopomorpha are partially defined by their synapomorphic leptocephalus larval stage, for which the nutritional requirements are not well understood. Characterizing the nutritional profile, including major nutrients (such as lipids) used for energetic processes, can help to gain a better understanding of the nutritional requirements for leptocephalus larvae. A total of 24 settl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…However, when there is a substantial depletion of endogenous nutrients, PLs are utilized to a greater extent for energy purposes. Storage lipids can be further categorized into short-term and long-term energy storage lipids, where short-term energy storage lipids like TAG are metabolized before long-term energy storage lipids such as WE-SE [40,41]. In this study, a significant decrease in TAG content was observed during the development of pearl gentian grouper yolk-sac larvae.…”
Section: Discussionmentioning
confidence: 59%
“…However, when there is a substantial depletion of endogenous nutrients, PLs are utilized to a greater extent for energy purposes. Storage lipids can be further categorized into short-term and long-term energy storage lipids, where short-term energy storage lipids like TAG are metabolized before long-term energy storage lipids such as WE-SE [40,41]. In this study, a significant decrease in TAG content was observed during the development of pearl gentian grouper yolk-sac larvae.…”
Section: Discussionmentioning
confidence: 59%
“…The strong association of the deep chlorophyll maximum and the thermocline within the eastern Caribbean exemplifies the nutritional benefits of thermocline associations for larval fish within The Bahamas [ 122 ]. The buoyancy of bonefish eggs and larvae [ 123 , 124 ] are most likely to have imparted the consistent relationship between the thermocline and mean dispersal depth. An instantaneous buoyancy rate of 8.5 m·d -1 at 0 h post-hatch (25 h post-fertilization) was calculated using the standard Stokes’ Law following the methods in McDonnell and Buesseler [ 125 ] with a larval density of 1.02 × 10 −5 kg·m -3 , head diameter of 2 × 10 −4 m, a length of 0.005 m [ 123 ], a dynamic viscosity of 0.959 kg·m -1·s [ 126 ], and a water density of 1024.4 kg·m -3 .…”
Section: Discussionmentioning
confidence: 99%